2012
DOI: 10.5604/15093492.1024716
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary views on the ossification of the ligamenta flava

Abstract: Wię za dła żół te są struk tu ra mi, któ re wraz z blasz ka mi łu ków krę go wych, bu du ją tyl ną ścia nę ka na łu krę gowe go. Bez po śred nie są siedz two z struk tu ra mi ner wo wy mi rdze nia krę go we go po wo du je, że ka żda pa to lo gia pro wa dzą ca do ich prze ro stu pro wa dzi w kon se kwen cji do za bu rzeń neu ro lo gicz nych. Jed ną z naj częst szych przy czyn ta kie go prze ro stu jest he te ro to po we kost nie nie. Głów ny mi re jo na mi świa ta do tknię ty mi tym scho rzeniem są kra je Azji,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Ligament hypertrophy is a common cause of spinal stenosis especially in the LF and can result in neural impingement and pain [72]. This process is thought to be driven by the ossification of the ligament in cases of high mechanical or other stressors [72].…”
Section: Spinal Pathologies Of Ligamentous Originmentioning
confidence: 99%
See 2 more Smart Citations
“…Ligament hypertrophy is a common cause of spinal stenosis especially in the LF and can result in neural impingement and pain [72]. This process is thought to be driven by the ossification of the ligament in cases of high mechanical or other stressors [72].…”
Section: Spinal Pathologies Of Ligamentous Originmentioning
confidence: 99%
“…Ligament hypertrophy is a common cause of spinal stenosis especially in the LF and can result in neural impingement and pain [72]. This process is thought to be driven by the ossification of the ligament in cases of high mechanical or other stressors [72]. Hypertrophic ossification of the LF involves replacement of fibroblasts with chondrocytes, necrosis, and alterations in collagen-proteoglycan content and structure [72].…”
Section: Spinal Pathologies Of Ligamentous Originmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, OLF is closely related to disturbance of the local mechanical microenvironment of the spine (12). The reduced stability of the middle and lower thoracic joints (T) due to long-term rotational motions has been indicated the anatomical basis of OLF (13). A previous study reported T9-T12 are the common segments affected by OLF, suggesting that increases in local stress caused by longitudinal axial instability of the middle and lower thoracic spine may be the biomechanical basis of OLF (14).…”
Section: Introductionmentioning
confidence: 99%
“…A significant role in pathological tissue calcification is attributed to mechanical stress (accumulation of microtrauma). The experimental studies performed on the spines of rats demonstrated that stretching and torsion movements result in the proliferation of cartilage tissue, transforming into bone tissue in the spinal ligaments [11,12]. Similarly, studies performed on patients exposed to stretching showed an increase in the rate of cytokines associated with the bone formation process (i.e., bone morphogenic protein, BMP) [11,12].…”
Section: Introductionmentioning
confidence: 99%